Trabalho em (re)construção: perspectivas das equipes multiprofissionais na Atenção Primária à Saúde em municípios do sertão de Crateús - Ce - Sousa, Janne Izabel Alves de (2024)
Multiprofessional work in public health policy, especially in Primary Health Care (PHC), is permeated by many challenges. In 2008, the inclusion of new professional categories with the creation of the Family Health Support Centers (NASF) led to the expansion and notoriety of these teams throughout Brazil, reaching 5,797 in 2018. However, since 2017, with the revision of the National Primary Care Policy (PNAB), the NASF had already experienced substantial changes. Subsequently, in November 2019, the publication of Ministerial Ordinance No. 2,979 instituted the Previne Brasil Program, established the new funding and costing model for Primary Health Care and interrupted discretionary funding for NASF-AB teams. In May 2023, Ministerial Order GM/MS No. 635 was published, instituting, defining and creating a federal financial incentive for the implementation, costing and performance of multi-professional teams in PHC. Given these facts, the main objective of this research was to investigate, from the point of view of the professionals, the working processes of the Multiprofessional teams in Primary Health Care in the municipalities of Ararendá, Crateús and Novo Oriente, and the specific objectives were to learn about the working processes of the Multiprofessional teams in Primary Health Care in Ararendá, Crateús and Novo Oriente; to understand whether the implementation of Ordinance 2.979, of November 12, 2019, has had an impact on their daily professional practices and to identify what perspectives these individuals envision for the future of their work in Primary Health Care. This is an exploratory qualitative study which, through intervention research, addressed the discourse of professionals linked to the teams mentioned using the Socioprofessional Questionnaire and Conversation Circles as tools. Critical Discourse Analysis (CDA) was used to analyze the data. By exploring the movement of multiprofessionalism in Primary Health Care, more specifically in the three scenarios studied, the research identified different working processes within the same team, impacts on health promotion and collaborative practices and different perspectives on the future of multiprofessional work in Primary Health Care.